ANALISIS ARAHAN PERSEBARAN SUMUR RESAPAN DI KOTA SURAKARTA TAHUN 2013 - santosa, erwin (Pendidikan Geografi, 2013)
The purpose of this study : (1) Knowing the shallow groundwater flow patterns in Surakarta (2) Knowing the runoff in Surakarta (3) Knowing the direction of the number and distribution analysis of infiltration wells in Surakarta. This study uses descriptive qualitative method carried out by the method of spatial approach. The results of this study were (1) Surakarta has a shallow groundwater flow direction is varied. There is a shallow groundwater basin morphology, ridge, and headed toward the river. Shallow groundwater flow direction is influenced by the volume of consumption society to shallow groundwater. Advance so that the height of the shallow groundwater is affected by population density and population activity. (2) Surakarta has a value of surface flow about 1179.8 m3/second with average 65.5 m3/second in 18 unit of land. (3) Referral number of infiltration wells in Surakarta were 483 infiltration wells. Referrals are based on the distribution of infiltration wells face height factor shallow groundwater, proximity to the river, and  land use.